Cryoglobulinemic vasculitis: from aetiology to treatment - G. Amati; A. Spinella; F. Lumetti; D. Giuggioli; G. Sandri (Verduci Editore, 2022)
Cryoglobulinemic vasculitis refers to a vasculitic syndrome affecting predominantly small-sized vessels that develops because of cryoglobulin presence in the serum. Cryoglobulinemic vasculitis is considered a rare disorder which, however, could be underestimated given the clinical polymorphism of the syndrome and the difficulty in achieving a diagnosis. In addition, the detection of cryoglobulins is an extremely complex process that depends on the expertise of the laboratory technician and on the possible presence of interfering components. A breakthrough in its etiological definition was the development of serological and biomolecular tests that allowed anti-HCV antibodies to be detected in serum and so to identify that the 86% of patients with mixed cryoglobulinemia was positive for circulating HCV-RNA. The diagnosis is supported by clinical and laboratory finding, according to the current classification criteria. The management of the disease depends on the severity of the systemic involvement, but in all HCV positive cases the eradication with new direct antiviral agents is mandatory. The aim of this review is to collect the principal knowledge about this particular disease, and to introduce the new further knowledge about classification, epidemiology and therapy strategies.